1993
DOI: 10.1002/j.2161-1920.1993.tb00169.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Counselor Disability and Reputation on Client Perceptions During a Career Counseling Session

Abstract: This study examined the effects of three counselor influence factors—expertness, trustworthiness, and attractiveness—on participants' impressions of a counselor during a counseling analogue situation. Using a 2 (counselor disability) x 2 (level of training) factorial design, no significant differences were found with respect to counselor social influence. These results are interpreted relative to the literature on perceptions of counselors with physical disabilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…In the past, studies attempting to measure the effects of reputation have not always shown expected results, possibly due to this factor. Indeed, Miller () attempted to measure the effects of counselors' reputations but failed to find a significant relationship. A possible factor in this was the operationalization of reputation within the sample.…”
Section: Reputationmentioning
confidence: 99%
“…In the past, studies attempting to measure the effects of reputation have not always shown expected results, possibly due to this factor. Indeed, Miller () attempted to measure the effects of counselors' reputations but failed to find a significant relationship. A possible factor in this was the operationalization of reputation within the sample.…”
Section: Reputationmentioning
confidence: 99%
“…Greenberg found that the experienced therapist was seen as significantly more attractive and receptive than the inexperienced one. Although not all of the more recent studies have found an association between reputational cues and perceived therapist credibility, the majority have found significant results indicating that experienced therapists are perceived as being more credible than less experienced ones (Conoley & Bonner, 1991;Littrell, Caffrey, & Hopper, 1987;Miller, 1993). Pooling together both the positive and negative results from this body of research, in the previously mentioned meta-analysis, Hoyt (1996) found a significant relationship between these two variables with a medium-sized effect in favor of experienced therapists (d = 0.51).…”
Section: Therapist Reputation and Perceived Credibilitymentioning
confidence: 99%